Evaluation of seasonal changes in fitness, anthropometrics, and body composition in collegiate division II female soccer players - Peart, A. N.; Nicks, C. R.; Mangum, M.; Tyo, B. M. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to investigate anthropometrics, body composition, aerobic and anaerobic fitness of collegiate Division II female soccer players throughout a calendar year. Eighteen (20 ± 0.9 years) National Collegiate Athletics Association division II female soccer players from the same team participated in the study. Anthropometrics and body composition variables were assessed in addition to the counter movement jump (CMJ), Wingate Anaerobic Test (WAT), and peak oxygen uptake (VO2peak). Data were collected over 5 time points: end of competitive seasons (ECS1 and ECS2), beginning of off-season (BOS), end of off-season (EOS), and preseason (PS). Repeated-measures analysis of variance was conducted to compare test scores among all 5 data collection points. Where appropriate, Bonferroni post hoc tests were used to determine which points were significantly different. Hip circumference decreased significantly (p < 0.001) from EOS (98.47 ± 6.5 cm) to PS (94.46 ± 6.8 cm). Fat mass (12.73 ± 5.4 kg) was significantly different in ECS2 compared with BOS and EOS means (p = 0.05) and percentage of body fat (%BF) (20.08 ± 5.44) significantly different in ECS2 compared with ECS1, BOS, and EOS means (p = 0.05), whereas fat-free mass (FFM) was maintained from ECS1 to ECS2. Counter movement jump, WAT, and VO2peak performance did not significantly change from ECS1 to ECS2. Anthropometrics and body composition results are similar to previous studies measuring Division II to professional female soccer players. Counter movement jump results remained consistent and are comparable to results on Division I female soccer players. Coaches and researchers can use these data to help design and evaluate training programs throughout a calendar year.